IMPLEMENTASI MANAJEMEN KAS UNTUK MENCEGAH KEGAGALAN KEUANGAN RUMAH TANGGA - Nuril Badria; Naimatul Hasanah; Dikri Minatur Rohmah; Hawi Riqi; Tri Setyo Budi Alan (Universitas Islam Malang, 2023)
Household financial management is the family's efforts to plan, implement, monitor and control the acquisition and use of family economic resources. Household financial management through simple bookkeeping is an important approach in managing family finances wisely. By recording income, identifying expenses, and planning a budget, families can control spending, increase savings, and achieve financial goals more efficiently. This service activity was carried out in Kalipare Village, Pitrang Hamlet. The majority of mothers in Kalipare village work as housewives so their income only comes from one source, namely their husband's salary. On the other hand, housewives never do simple bookkeeping in managing their finances, so their expenses are often greater than their income. Based on this problem, community service was carried out to the Kalipare village community to assist and provide outreach and education regarding cash management. This service aims to increase people's insight into the importance of financial management in the household so that failure in managing household finances does not occur. The methods used in socializing household finances are socialization methods, counseling methods, training and discussion methods, and evaluation. The results of household cash management outreach activities for the people of Pitrang hamlet are reducing problems in managing household finances and being able to help the community in preparing simple bookkeeping.